(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The article discusses the notion of ancestry as a philosophical principle intrinsic to black Brazilian performance, without detaching itself from the dimension of a political and contemporary scene. The artist-researcher starts from the creative process of her solo Sobretudo Amor, in which the dimension of practical and philosophical experience with ancestrality guided the creative process and broadened its reading possibilities. Ancestry anchored in the dimensions of deterritorialization and reterritorialization are the artist’s propositions and reflections populated in this research, which was developed as part of the Doctorate in Performing Arts at PPGAC-UFBA.